Using a Suggested Strategy for Electronic Hajj Reservation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Everyone knows the extent of the importance of Hajj in the life of every Muslim, as it isone of the obligations of Islam and one of its five pillars, and it is imposed on every adult Muslim whocan perform Hajj for once in his life and it is a command from God that will not change and will notchange and will not stop and use all methods to facilitate this obligation and all modern technologies and techniques to serve the pilgrims in a continuous manner forever. On the other hand, to keep the Hajj away from all worldly subjects and make the Hajj ritual with the utmost transparency, also Permission to perform Hajj must be not permitted Hajj to a specific group according to a party or official in the state or those have money and influence or granted to people who performed this duty more than once time at the expense of other people that did not perform Hajj before due to the lack of an opportunity to perform the Hajj rituals due to the use of the lottery mechanism in the distribution. This was the idea of this application for the Hajj and Umrah Authority in the Kingdom of Saudi Arabia to be responsible or for this body to be a global Hajj organization whose representatives are chosen from every country in the world, and the Muslim registers directly in the application and gets the result directly without interference by any party Official and according to the points obtained through the information entered by any person who registers in Al-Hajj Registration Application.